Analysis of the economic impact of implementing VAT and import duties on the Indonesia-Japan premium beef trade under the IJEPA-FTA scheme: A CGE-GTAP approach - Firdiansyah, Akhmad; Hashfi, Hasbiul; Gultom, Yulifar Amin (Educoretax, 2024)
The implementation of import policy raises critical questions related to fiscal and economic aspects, especially regarding the impact of imposing import VAT without exemption facilities and import duties on premium beef imports for the Indonesian economy. This study investigates the effects of taxation tariffs on premium beef from Japan. This research is a quantitative study using a disaggregated Computable General Equilibrium Global Trade Analysis Project (CGE-GTAP) analysis. It focuses on the impact of predictor simulations on economic variables consisting of GDP, exports, imports, trade balance, equivalent variation, domestic production and demand, and prices. The study compares scenarios when VAT is imposed, when import duty preference under IJEPA is applied, and when VAT is imposed and import duty rates are increased to protect domestic producers. The results of this study show that the impact of the IJEPA agreement between Indonesia and Japan, especially regarding the import of premium beef, benefits both parties, even though the tariff regulated in IJEPA for premium beef is the same as the MFN tariff. There was an increase in GDP, imports, trade balance, domestic production and demand, and prices, but exports and welfare declined. Both simulations showed similar results, but the increase in import duties demonstrated a greater magnitude. This means that producers experience a greater positive impact, but consumers suffer greater losses as well. This study demonstrates that the imposition of VAT accompanied by import duty rates in IJEPA can have a positive effect on the national economy. It is recommended to continue this policy.